Transcrustal Compressible Fluid Flow Explains the Altiplano‐Puna Gravity and Deformation Anomalies. Issue 16 (18th August 2022) - Gottsmann, J.; Eiden, E.; Pritchard, M. E.
Abstract: Enigmatic large‐scale (>150 km wide) ground deformation in southern Bolivia has been ongoing for more than 50 year. Concurrent changes in gravity recorded between 2010 and 2018 imply minor changes in subsurface density in the absence of significant mass changes. Numerical modeling of the gravity changes and concurrent InSAR LOS displacements gives annual bulk density changes of 0.002 kg m −3 in the Altiplano‐Puna Magma Body (APMB) and −0.03 kg m −3 in a vertical bulge‐column ensemble beneath Uturuncu volcano. We propose that the transcrustal migration of fluids from the APMB to shallower crustal levels by compressible flow is the source of ground deformation. Localized ground subsidence south of Uturuncu can be best explained by a density decrease of 20 ± 5 kg m −3 between 2011 and 2013 in a hydrothermal reservoir. Our findings contribute to the growing recognition of transcrustal fluid migration as a source of volcanic unrest. Plain Language Summary: Large‐scale (>80 km wide) anomalous ground uplift has been observed in the Altiplano‐Puna region of southern Bolivia for more than five decades, but there is no consensus on the underlying causes. While magma migration and emplacement at shallow depth or a combination of magma and fluid migration have been proposed, none of the previous studies considered changes in the gravity field. Here, we report on temporal and spatial changes in gravity observed between 2010 and 2018 which primarily indicate subsurface density changes as the cause of ground deformation during that period. Using computer modeing, we show that the ascent of fluids from a deep‐seated (∼20 km below the ground surface) magma reservoir through the overlying crust can explain both the deformation and gravity changes. This ascent occurs amid a decrease in confining pressure, leading to the expansion of the fluids within a volume best characterized by a column‐like geometry. Movement of magma is either negligible or absent. Localized ground subsidence can be explained by the release of the fluids to the surface. Key Points: We report gravity changes between 2010 and 2018 from the Altiplano‐Puna deformation anomaly Numerical modeling highlights minor density changes in the subsurface magmatic plumbing system 2010–2018 deformation best explained by transcrustal migration of compressible magmatic fluids